4
$\begingroup$

$\phi (t)=\sum_{n=0}^{\infty}e^{tn}\cdot \frac{\lambda^{n}}{n!}e^{-\lambda}$

$=e^{-\lambda}\sum_{n=0}^{\infty}\frac{(e^{t}\lambda)^{n}}{n!}$

$=e^{-\lambda+\lambda e^{t}}$ I'm confused here as how $\sum_{n=0}^{\infty}\frac{(e^{t}\lambda)^{n}}{n!}$ simplifies to $e^{\lambda e^{t}}$, can someone please explain?

$\endgroup$
  • $\begingroup$ Taylor: $e^y=\sum_{n=0}^\infty y^n/n!$. Take $y=e^t\lambda$. $\endgroup$ – Zen Jun 10 '14 at 3:57
3
$\begingroup$

[Edit: Perhaps the easy way to see it is to try it backwards. Expand $\exp(\lambda e^t)$ as a series in $(\lambda e^t)$.]

Its straight from the series for $\exp(x)$

$$\exp(x) = 1 + x + \frac{x^2}{2!}+ \frac{x^3}{3!} + ... = \sum_{n=0}^\infty \frac{x^n}{n!}$$

Note that in that series, $x$ is a constant; the dummy variable is $n$. So as long as the sum converges, any other constant will work just as well. Since the series converges for any finite argument, that works without any problem.

So for example $\sum_{n=0}^\infty \frac{f(w)^n}{n!} = \exp(f(w))$, as long as $f(w)$ is finite ... so it works for any finite value $f(w)$.

Now if $x= \lambda e^t$, you get your expression.

That is, that's the series for $\exp(\lambda e^t)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.